Polycyclic aromatic hydrocarbons in commercial squids from different geographical origins: levels and risks for human consumption - Gomes, Filipa (2014)
The concentrations of 18 polycyclic aromatic hydrocarbons (PAHs) were determined in five commercially valuable squid species from different geographical origins (Atlantic, Indic and Pacific Oceans). Out of the 18 quantified PAHs (the 16 PAHs considered by US EPA as priority pollutants, dibenzo(a,l)pyrene and benzo(j)fluoranthene) only dibenz(a,h)anthracene was not detected. The total concentrations of PAHs varied by a factor of more than 100-fold, from 0.22 (Loligo gahi) to 60.9 lg/kg ww (Loligo reynaudii). Intraand inter-specific variability of PAH levels was statistically assessed. Nine carcinogenic (probable/possible) PAHs accounted for 1% (L. reynaudii) to 26% (Loligo opalescens) of the total PAHs content being the main contributors naphthalene (in Loligo duvaucelii, L. reynaudii and Loligo vulgaris species), chrysene (in L. opalescens) and indeno(1,2,3-cd)pyrene (in L. gahi). PAHs source analysis indicated that four of the five zones of capture of the different squid species are significantly affected by both petrogenic and pyrolytic sources. Assessment of the target carcinogenic risks, established by the US EPA, suggested that L. gahi (Atlantic Ocean) and L. opalescens (from Pacific Ocean) may pose additional risks for consumers, if not eaten in moderation, derived from benzo(a)pyrene ingestion.